AVALIAÇÃO CURRICULAR: A FILOSOFIA DA EDUCAÇÃO NA LICENCIATURA EM PEDAGOGIA DA UEPG - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This work presents the result from the curricular component Philosophy of Education. The aim of the research was analyze contributions of the subjects Philosophy of Education I and II from the curriculum of the Faculty in Pedagogy of the State University of Ponta Grossa (Universidade Estadual de Ponta Grossa – UEPG in Portuguese acronym), for professor training. The research was carried out from the following matter: What are the contributions from the curricular component Philosophy of Education that integrates the curriculum of the graduation in Pedagogy at UEPG, for pedagogue training? The following specific objectives were defined: discussing the curricular evaluation theoretical and methodological assumptions in a dialogue with reference authors in the area; presenting a historical panorama on the Education Philosophy of the Faculty in Pedagogy of the UEPG; understanding the contributions from teaching Education Philosophy by pointing its possibilities and limits for teachers initial training (pedagogue), in the Faculty in Pedagogy offered in UEPG campus. The research field was the UEPG. Participant subjects were: a) professors who lectured the subject Philosophy of Education in the faculty of Pedagogy (2005 to 2016); b) students enrolled in 2016 and 2017. Temporary clipping occurred due to the publication of resolutions 01/2002, 02/2002, 01/2005 and 02/2015 – all of them related to the professors‟ training. The research was performed in a qualitative approach, evaluative case type of study. The procedures for data collection were semi structured interviews, participant observation, questionnaire and documental research. Theoretical reference was built in dialogue with reference authors regarding to the epistemological assumptions of education and curricular evaluations, such as Brandalise (2010), Cappelletti (2002; 2010),, Lewy (1979) ), Machado (2013), Rodrigues (1995) and Sacristán (2000; 2008; 2013), related to the curricular studies. The main results pointed to: documental analysis enabled a historical panorama of Philosophy and Philosophy of Education within UEPG course, and characterizing subject programs based on Philosophy of Education; the curriculum evaluated enabled identify and understand the curriculum movement, regardind to DCN (National Curriculum Guidelines in Portuguese acronym) and to the PPC (Pedagogical Project of the course also in Portuguese acronym), to the possibilities for modeling, teaching practice and practice reflections; studies in Philosophy of Education are fundamental for the Pedagogue training; the contents approached initiated reflections, analysis and learning processes; the relevance and contribution of bibliography selected by lecturers to understand the contents studied. Among limitations identified, we highlight: Philosophy and Philosophy of education devaluation; lecturers participant in the research considered the importance of Philosophy dialogue with other areas; however, it still not happened in the current curriculum; students attributed higher percentile for regular criteria for learning evaluation instruments, and the higher negative percentile for teaching methodology and integration with the subject Fundamentals‟ lecturers; students not always understand the complexity of teaching practice. The research confirmed that curriculum evaluation field is open for new studies. We intend this research as a path for future researches on Philosophy of Education, from the specific reference about Philosophy [of Education].
Keywords: Avaliação; Avaliação Curricular; Filosofia da Educação; Licenciatura em Pedagogia; Evaluation; Curriculum evaluation; Philosophy of Education; Undergraduation in Pedagogy; CNPQ::CIENCIAS HUMANAS::EDUCACAO